The Effect of Instagram Digital Promotion and Customer Experience on Purchasing Decisions on the Alfagift Application in Baleendah Bandung Regency - Isni Suci Ramdina; Rizka Aula Assaf (Escalate : Economics and Business Journal, 2026)
Digital transformation and social media have significantly affected consumer purchasing patterns, especially in e-grocery applications like Alfagift. This study aims to examine the influence of Instagram digital promotion and customer experience on purchasing decisions among Alfagift users in Baleendah, Bandung Regency. The research used a quantitative approach with a causal associative method. A total of 100 respondents aged 17–35 years who had used Alfagift in the past three months were selected through non-probability sampling. Data were collected using a structured questionnaire and analyzed using classical assumption tests, multiple linear regression, and hypothesis testing. Results show that both Instagram digital promotion and customer experience have positive and significant effects on purchasing decisions, explaining 54.6% of their variation. The findings indicate that improved digital promotion quality and user experience can significantly increase consumers’ willingness to purchase through Alfagift. The conclusion emphasizes the importance of optimizing digital marketing content and app usability to enhance consumer loyalty.